Comparison of aspiration versus combined technique as first-line approach in terminal internal carotid artery occlusion: a multicenter experience. (4th August 2021) - Diana, Francesco; Vinci, Sergio Lucio; Ruggiero, Maria; Semeraro, Vittorio; Bracco, Sandra; Frauenfelder, Giulia; Paolucci, Aldo; Cirillo, Luigi; Pesce, Alessandro; Tessitore, Agostino; Commodaro, Christian; Ganimede, Maria Porzia; et al.
Abstract : Background: There is no consensus on the most effective endovascular technique to use in patients with acute ischemic stroke due to terminal internal carotid artery (ICA) occlusion. The aim of this study was to compare safety and efficacy of the aspiration technique (AT) and combined technique (CT) as first-line approach in terminal ICA occlusions. Methods: We performed a retrospective analysis of prospectively collected databases from seven Italian stroke centers. Patients were divided into two subgroups according to the first-line approach: AT group or CT group. We followed the STROBE guidelines for cohort studies. We used Chi-square test, one-way and multivariate ANOVA analysis, together with contrast analysis and post hoc tests, logistic regression and Pearson's bivariate correlation for the statistical analyses. Results: Between January 2018 and August 2020, 353 patients were treated for a terminal ICA occlusion, with either AT or CT. CT was associated with a higher Thrombolysis in Cerebral Infarction (TICI) 2B-3 after the first pass (51.0% vs 26.9%) and at the end of the procedure (84% vs 73.3%) and with an improved clinical outcome at discharge (modified Rankin Scale (mRs) 0–2 of 47.8% vs 34.0%) and at 3 months' follow-up (mRs 0–2 of 56.5% vs 38.9%) compared with AT. Conclusion: Thrombectomy of terminal ICA occlusions obtained using CT as first-line approach demonstrated better technical and functional outcomes in comparison with AT.